Legal Protection for the Implementation of Diversion in Narcotics Crimes Based on Decree Number 1/PID.DIV/2023/PN.CBN - Bustaman, Bustaman; Aulia Rahman (Jurnal Justice Aswaja, 2023)
This study aims to determine and analyze the regulation of legal protection for children who abuse drugs based on Decree Number 1/Pid.Div/2023/Pn.Cbn and the process of legal protection for children as drug abusers at the Cirebon District Court. This type of research is normative legal research. Based on the discussion, it is concluded that the legal protection carried out for children as drug abusers in Indonesia based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System has been regulated starting from the process of investigation, arrest, detention, prosecution, examination in court and correctional facilities. Legal protection for children at all levels is carried out by seeking to fulfill various children’s rights during the criminal justice process, as well as seeking to prevent children from being punished by resolving cases outside the court through diversion. The Cirebon District Court has attempted to carry out the process of legal protection for children as drug abusers by referring to Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. Child Judges strive to realize the legal protection process by fulfilling children’s rights during the examination process, as well as seeking to resolve cases through diversion. However, the efforts of child judges in the child legal protection process are still not optimal because it turns out that there are still many violations of children’s rights and there are still many children who abuse narcotics who are processed through criminal justice, and end up with punishment.